Woman in the Bible - Guinsburg, Jacó (2013)
This article discusses the figure and the representation of the woman in the Bible. They are crowd in the biblical account. Since Eve, each page there is a woman's face. Virtuous or sinner, selfless or soulless, suit or tyrannical, he raises, as once today, living a printing temperament, a gesture, a feeling. The subtle game of psychology and female motivations, its relations with the masculine world, continues pounding on the heroines of the Scriptures.